Impacts of monetary policy shocks on the domestic and foreign banks in Malaysia - Kassim, Salina; Abdul Manap, Turkhan Ali (IIUM Press, 2009)
This study investigates the impact of monetary shocks on bank loans extended by local banks and foreign banks in Malaysia over the period from January 1991 to December 2006. It adopts the impulse response functions and the variance decomposition analysis to study the responses of lending by these banks to monetary policy shocks. The study finds that foreign banks do not react negatively to monetary policy shocks and do not abandon the domestic market in times of economic distress. The different responses of the balance sheet items of these banks have several important implications, particularly on monetary policy implementation and risk management practices of the banks.